Two New Records of Species and A New Synonym of Genus Typhonium (Araceae) For Flora of Indochina - Du, Nguyen Van; Anh, Nguyen Thi Van; Tien, Tran Van; Toan, Le Chi (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 3DO - 10.25073/2588-1140/vnunst.5321, 2022)
Two species of the genus Typhonium are described as the new species for the Flora of Indochina. T. cordifolium was discovered for the first time in Cambodia and Vietnam and  T. khonkaenensis was found for the first time in Vientian of Laos. In the paper, the name  T. rhizomatosum Galloway & Schmidt is recorded as a new synonym of T. cordifolium S. Y. Hu, while T. khonkaenensis is confirmed as a separated species in the genus Typhonium.